EFFECT OF ADDING ALOE VERA EXTRACT ON THE QUALITY OF BUFFALO OOCYTES USING TWO CRYOPRESERVATION METHODS - H.T.A., Alkhazraji,; H.J.H., Banana,; M-B.M.R.Fakhrildin, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to evaluate the impact of two types of cryopreservation and different concentrations of Aloe vera as an antioxidant (0,10% and 20%) on the viability and normal morphology of immature and in vitro mature buffalo cryopreserved oocytes. The in vitro mature and immature oocytes were kept in cryopreservation solutions for rapid and vitrification techniques. The results revealed that the proportion of buffalo oocytes found to be viable and normal morphology were significantly (P